CLASSIFICATION, CLINIC, AND DIAGNOSIS OF ORBITAL FRACTURES (LITERATURE REVIEW) - Gafurov Z.A. (Scholar Express Journals, 2023)
Contusion trauma of the orbit is characterized by particular severity, high risk of blindness, the possibility of purulent-inflammatory complications, functional and cosmetic defects [1]. The multiple nature of traumatic injuries leads to the need to use accurate topical diagnosis and plan treatment. The study of traumatic lesions of the orbit is relevant
Keywords: orbital contusion trauma; fractures; eye sockets; facial skeleton